KEPENTINGAN INDONESIA BEKERJASAMA DENGAN TURKI DALAM INDUSTRI PERTHANAN (STUDI KASUS: PEMBUATAN TANK MEDIUM) - Alfita Wulandari; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aimed to describe why Indonesia agreed corporate with Turkey in producing Medium Tank. This corporation was held because Indonesia need to increase and modernize its army defense. The cooperation consist of three steps, Design, Prototyping, and Producing. The signed of MoU, has been done between the two countries since June 2010.In this research, Researcher analyzed this case using qualitative methods to find data and facts through some literature. The literature collected from books, journals, mass media and websites. Researcher use realism perspective which believe all policies issued by the state is an attempt to achieve or defend the national interest. The level analysis of the research is nation-state and also use national interest theory by Donald Edwin Nuctherlain.From this research it can be seen, Indonesia choose Turkey as a partner in producing Medium Tank because of Indonesia’s needs to increase the Indonesia’s military industry. Military industry cooperation made a major impact on changes in military technology by the armed forces of the Republic of Indonesia. Indonesia gain its interest to modernized army technology system (Alutsista) and increase its army defense.Keywords: Interest, International Cooperation, Defense, Alutsista, Medium Tank